Implementation of Gyro Accelerometer Sensor for Measuring Respiration Based on Inhale And Delphi Based Exhale - Egan Graha Utama; Triwiyanto Triwiyanto; Triana Rahmawati; Vugar Abdullayev; Mohanad Abdulhamid (Jurnal Teknokes, 2023)
Gyro accelerometer sensor which is a sensor that can detect changes in position and speed. Many studies use the gyro accelerometer sensor as a sensor in respiration. This study aims to examine and analyze changes in the position of inhale and exhale in 3 positions of the gyro accelerometer sensor which is placed on the abdomen and chest to determine the value of respiration. This study displays 3 signals and respiration values detected by the gyro accelerometer sensor and then displayed using Delphi. The independent variable in this study is the value of respiration, while the dependent variable is the output of the gyro accelerometer sensor. The biggest error value from the module measurement is when the sensor position 2 is sitting with an error value of 1.11%. While the error value is greatest when the sensor position 3 is in a sleep state with an error value of 3.66%. The conclusion from these results is that the module has a relative error (error value) that is still within the allowable tolerance limit, which is ±5%. This study also shows the effect of the gyro accelerometer sensor output value on the placement of the 3 sensor positions placed on the abdomen and chest. This study has limitations, namely when the respondent moves or walks in a place where there is still noise and the signal on the Delphi display is lost.